2015
DOI: 10.18632/oncotarget.4199
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic cell kinase (HCK) as a therapeutic target in immune and cancer cells

Abstract: The hematopoietic cell kinase (HCK) is a member of the SRC family of cytoplasmic tyrosine kinases (SFKs), and is expressed in cells of the myeloid and B-lymphocyte cell lineages. Excessive HCK activation is associated with several types of leukemia and enhances cell proliferation and survival by physical association with oncogenic fusion proteins, and with functional interactions with receptor tyrosine kinases. Elevated HCK activity is also observed in many solid malignancies, including breast and colon cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
93
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(99 citation statements)
references
References 189 publications
(166 reference statements)
5
93
0
1
Order By: Relevance
“…HCK, a Src family tyrosine kinase and a direct target of ibrutinib, could enhance tumor‐associated macrophage migration and matrix remodeling to promote invasive capacity of tumor cells in a MMP‐dispensable manner . Although there is no related studies regarding the biological functions of HCK in HCC, it has been reported that HCK activation played important roles in podosome formation which contributed to cancer cell dissociation from the primary tumor and seeding into distal organs . The mutation of p.V174M in HCK takes place in the SH2 domain, which conformation is crucial for the HCK protein activation; therefore, this mutation may lead to abnormal activation of HCK, which could promote tumor cell invasion.…”
Section: Resultsmentioning
confidence: 99%
“…HCK, a Src family tyrosine kinase and a direct target of ibrutinib, could enhance tumor‐associated macrophage migration and matrix remodeling to promote invasive capacity of tumor cells in a MMP‐dispensable manner . Although there is no related studies regarding the biological functions of HCK in HCC, it has been reported that HCK activation played important roles in podosome formation which contributed to cancer cell dissociation from the primary tumor and seeding into distal organs . The mutation of p.V174M in HCK takes place in the SH2 domain, which conformation is crucial for the HCK protein activation; therefore, this mutation may lead to abnormal activation of HCK, which could promote tumor cell invasion.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, excessive activation of endogenous SFK results in a lethal autoimmune response in Lyn CA mice (Hibbs et al, 1995) and inflammatory lung disease in Hck CA mice (Ernst et al, 2002). The latter phenotype can be rationalized by the presence of Wasp, Cbl, paxilin, and other Hck substrates in adhesion and migration complexes (Poh et al, 2015), and the capacity of Hck to mediate β1/2 integrin-dependent outside-in signaling and to facilitate the formation of podosomes (Kovács et al, 2014). However, we note that despite the more aggressive growth of tumors in Hck CA , the extent of TAMs remained comparable.…”
Section: Discussionmentioning
confidence: 99%
“…Several scaffolds for targeted HCK inhibition are in development based on prior work implicating HCK in the pathogenesis of several solid and hematologic malignancies, as well as productive HIV infection. 41,42 In addition to inhibiting other SRC family members, dasatinib also shows potent inhibition of HCK and may be active in diseases dependent on mutated MYD88. 43 In conclusion, our findings suggest that HCK is a downstream target of mutated MYD88, is activated by IL-6, and triggers pro-survival signaling including PI3K/AKT, MAPK/ERK, and BTK in MYD88-mutated cells.…”
Section: Cc-292mentioning
confidence: 99%